Improving the Quality of PAI-BP Learning in the Independent Curriculum Through the Implementation of the Portfolio Learning Model - Junaidi Marbun; Dewi Sarina; Ahmad Sabri; Sasmi Nelwati (al-Afkar, Journal For Islamic Studies, 2025)
The objective of this study was to evaluate the effectiveness of the portfolio learning model at SMPN 21 Satu Atap Teluk Bintan in enhancing the quality of PAI and BP learning. Employing qualitative research with descriptive methods, the study focused on improving the quality of PAI and BP learning, encompassing the learning process and outcomes. The study involved participation from PAI subject teachers and seventh-grade students at SMPN 21 Satu Atap Teluk Bintan. Data was collected through interviews, documentation studies, and observations, and subsequently analyzed through three stages: data reduction, data presentation, and data verification. The results indicated that the implementation of the portfolio learning model in PAI and BP subjects encourages active student engagement, elevates motivation to complete assigned tasks, and enhances comprehension of the lesson material. Therefore, optimizing teacher competence to effectively utilize a variety of learning resources is essential in achieving optimal learning objectives.